Failure analysis of the multi-level series rotary seal device under high-pressure water - Liu, Zenghui (Strojniški vestnik, 2017)
High-pressure water jets are used to assist roadheaders in breaking hard rock. The failure life of the high-pressure rotary seal (HPRS) is significant, due to how it affects the safety and efficiency of the roadheader. Here we investigate the mechanical behaviour of the HPRS with a series of experiments. Single-level rotary seal device based studies were conducted to investigate the effect of seal forms, materials, operating pressure and spindle speed on friction torque and leakage. The best seal form from the three kinds of forms was chosen to test the failure life of the multi-level series rotary seal device and the relationships between the operating pressure, spindle speed, temperature, leakage and failure life were analysed. The failure life of rotary seals from Levels 1 to 4 was observed to be 15, 11, 5, and 4 days respectively. The increase in temperature of Levels 1 and 2 was perceived to be slow at the beginning phase of the test, while it rose sharply until the failure occurred, whereas in the case of Levels 3 and 4 it was instantaneous.
Keywords: analiza odpovedi; mehansko preizkušanje; obraba; rotacijsko tesnilo; visok tlak